Effect of feeding bypass protein with and without biopromotors on milk production, and certain rumen and blood metabolites in lactating Murrah buffaloes - Akbar, M A; Kuldip, Kuldip; Kumari, R; Singh, N (The Indian Journal of Animal Sciences, 2012)
An experiment was conducted to assess the effect of feeding bypass protein with or without biopromotors on milk production and certain rumen and blood metabolites in 25 lactating Murrah buffaloes. The animals were randomly divided into 5 groups of 5 each on the basis of nearness in body weight, lactation length and daily milk yield following a completely randomized design. The experiment was carried out far a period of 90 days. The animals in control group (Tâ‚) were fed conventional concentrate mixture as per their requirement. In group Tâ‚‚ , 10 g biopromotors (consisting of live yeast culture) were fed with the concentrate mixture of Tâ‚ In group Tâ‚ƒ , animals were fed 50% conventional concentrate mixture to that of Tâ‚ and the remaining protein requirement was met by supplementing the ration with the whole concentrate treated with formaldehyde. In group Tâ‚„, animals were fed as in Tâ‚ƒ along with 10 g biopromotors. In group Tâ‚…, animals were fed 200 g commercially available mixture of bypass protein and biopromotors (containing Saccharomyces cerevisae 1.4 x 10â¹ m cfu along with growth medium 10g , niacin 1 g, selenium 2.5 g and full fat soya protected bypass protein 188.75 g) and the remaining protein requirement was met through conventional concentrate mixture of control diet (Tâ‚). All the experimental buffaloes were offered green jowar and wheat straw to meet their total DM and energy requirement. An increase (P